Electrochemical oxidation of the phenolic benzotriazoles UV‐234 and UV‐327 in organic solvents - Chan, Ya Yun (2020)
The electrochemical behavior of selected phenolic benzotriazoles (BZTs), namely 2‐(2H‐benzotriazol‐2‐yl)‐4,6‐bis(1‐methyl‐1‐phenylethyl)phenol and 2,4‐di‐tert‐butyl‐6‐(5‐chlorobenzotriazol‐2‐yl)phenol (commercial names UV234 and UV327, respectively) were examined with cyclic voltammetry (CV) and controlled potential electrolysis (CPE) in acetonitrile and dichloromethane solutions. CV indicated that both phenolic BZTs undergo a chemically irreversible oxidation process at approximately Ep°x=+1.0 V vs. Fc/Fc+ (where Ep°x is the anodic peak potential and Fc=ferrocene) to form compounds that cannot be electrochemically converted back to the starting material on the voltammetric timescale. In basic conditions, cyclic voltammetry experiments indicated that the corresponding phenolates (prepared by reacting the phenols with equiv. mols of n‐Bu4NOH) were oxidized at Ep°x∼−0.2 V vs. Fc/Fc+ via a one‐electron diffusion controlled process with anodic (ip°x) to cathodic (ipred) peak current ratios (ip°x/ipred)≫1, suggesting that the produced phenoxyl radicals decomposed rapidly via a chemical step. However, electron paramagnetic resonance (EPR) experiments performed on the bulk electrolyzed solutions of the phenolates after one‐electron bulk oxidation indicated long lifetimes of the UV234. and UV327. phenoxyl radicals. Therefore, the long timescale CPE and spectroscopic (UV‐vis and EPR) studies provided good evidence of a reversible dimerization mechanism between the phenoxyl radicals, which explained the apparent discrepancy with the short timescale CV experiments.